Saudi Arabia : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
The authorities responded quickly and decisively to the COVID-19 crisis and the economy is recovering. COVID-19 cases are well below the 2020 peak and vaccination is progressing. The exit from the remaining COVID-related policy support needs to be carefully managed and the Vision 2030 reform agenda continued.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Saudi Arabia